Student nurses' experiences regarding their clinical learning opportunities in a public academic hospital in Gauteng province, South Africa - Mpho N. Motsaanaka; Agnes Makhene; Hafisa Ally (AOSIS, 2020)
Background: During the training of student nurses, clinical placement is a compulsory requirement, as it exposes them to learning opportunities for the acquisition of clinical skills. This prepares them to become safe and competent professional nurses. However, the increased intake of student nurses in the Gauteng nursing colleges led to overcrowding in a public academic hospital, thus negatively influencing their learning experiences and availability of clinical learning opportunities. Aim: The purpose was to explore and describe the student nurses' experiences regarding their clinical learning opportunities to make recommendations to enhance their clinical learning opportunities in order to address the optimisation of their learning experiences. Methodology: A qualitative, exploratory, descriptive and contextual research design was used. A purposive sampling method was used to select second-year student nurses registered in the Regulation (R425) programme for qualifying as a nurse (general, psychiatry and community) and midwife, as they would have acquired at least 1 year of clinical experience. Four focus groups, which comprised six to eight participants, were constituted, and research was conducted until data were saturated. Field notes were simultaneously taken to enrich the data collected. Thematic coding of qualitative data was used. Principles of trustworthiness and ethical principles were adhered to. Results: The study revealed four themes. Three were negative experiences that included overcrowding, negative emotional experiences of student nurses and challenges of professional nurses. A theme concerning positive experience entailed knowledge-sharing amongst various health care disciplines. Conclusion: It was evident that student nurses had more negative emotional experiences than positive experiences. Therefore, the need to enhance their clinical learning opportunities in order to address the optimisation of learning experiences is eminent.